Optimizing the Region for Evaluation of Global Gamma Analysis for Nasopharyngeal Cancer (NPC) Pretreatment IMRT QA by COMPASS: A Retrospective Study - Lu, Wenli; Li, Ying; Huang, Wei; Cui, Haixia; Zhang, Hanyin; Yi, Xin (Frontiers in Oncology, 2022)
Background: The global gamma passing rate is the most commonly used technique for patient-specific pretreatment quality assurance in radiation therapy. However, the optimal region for evaluation and specific action limits need to be explored. Therefore, this study was carried out to explore the optimal region for evaluation of the global gamma passing rate and define action limits by COMPASS. Methods: A total of 93 IMRT plans for nasopharynx cancer (NPC) patients were selected for retrospective analysis. Firstly, the dose distribution was divided into six regions (‘10%’, ‘20%’, ‘30%’, ‘40%’, ‘50%’, ‘60%’) and one clinical-oriented region (‘whole’) to perform the global gamma re-analysis. Meanwhile, the percentage gamma passing rate (%GP), mean gamma index (mGI) and percentage dose error (%DE) of the dose volume histogram metrics were recorded by COMPASS application based on 3%/2mm criteria. Secondly, the pearson’s correlation coefficient was used to analyze the correlation between the %GP/mGI and %DE in different regions. Finally, the plans introduced with MLC errors were prepared for validation. Besides, we also compared the positive rate of %GP/mGI action limits in detecting MLC-error-introduced plans in different regions. Results: (1) The γwhole, γ10%, γ20%, γ30%, γ40%, γ50%, γ60% were found to be correlated with 4, 2, 1, 1, 1, 1 and 3 out of 10 %DE, respectively. The mGIwhole, mGI10%, mGI20%, mGI30%, mGI40%, mGI50%, mGI60% were found to be correlated with 5, 3, 0, 1, 1, 4 and 2 out of 10 %DE, respectively. (2) According to the Youden Coefficient, we defined the action limits (AL) of γwhole ≥ 92%, mGIwhole ≤ 0.36, mGI40% ≤ 0.43, mGI60% ≤ 0.40 respectively. (3) In the validation, for original plans, the accuracy of ALγwhole, ALγ10%, ALmGIwhole, ALmGI40%, ALmGI50% and ALmGI60% was 23%, 9.8%, 90%, 80.3%, 9.8% and 88.5%, respectively. For test plans with systematic MLC-errors smaller than 0.8mm, the positive rates of ALγwhole, ALγ10%, ALmGIwhole, ALmGI40%, ALmGI50% and ALmGI60% were 25%, 58%, 92%, 92%, 42%, 100%, respectively. Conclusions: Compared with the traditional evaluation region, the ‘whole’ region is more meaningful to the clinic. The study has also showed that mGIwhole is able to provide more information for validation results.